2022
DOI: 10.1177/10525629221126129
|View full text |Cite
|
Sign up to set email alerts
|

Bringing “Class” into the Classroom: Addressing Social Class Privilege Through Management Education

Abstract: Research increasingly acknowledges the far-reaching impact of social class and the many ways in which it can meaningfully shape individuals’ work and working lives. As such, social class and concomitant class privilege represent relevant and necessary content for the management classroom. In this paper, we begin by offering an overview of select research addressing social class and work, which helps to emphasize the significance of social class in organizational life. Next, to help educators bring “class” into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…First, higher education institutions can foster individuals’ perception of sociocultural belonging irrespective of their social class origin (Stephens et al, 2014b; Walton & Cohen, 2011). Educators in business schools might start to reflect how their own assumptions (e.g., of independence as cultural norm) unconsciously reproduce class differences in the classroom (Moergen & Kish-Gephart, 2023). For instance, Silverman and colleagues (2023) show that if educators communicate students’ lower social class backgrounds as sources for unique strengths, students subsequently start to increase their academic achievements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, higher education institutions can foster individuals’ perception of sociocultural belonging irrespective of their social class origin (Stephens et al, 2014b; Walton & Cohen, 2011). Educators in business schools might start to reflect how their own assumptions (e.g., of independence as cultural norm) unconsciously reproduce class differences in the classroom (Moergen & Kish-Gephart, 2023). For instance, Silverman and colleagues (2023) show that if educators communicate students’ lower social class backgrounds as sources for unique strengths, students subsequently start to increase their academic achievements.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, a large body of research has shown that prevalent cultural norms of independence in education reinforce initial class-based disadvantages (e.g., in management education, see Moergen & Kish-Gephart, 2023). As such, while gateway contexts could enable social mobility, cultural mismatches likely increase the barriers for individuals from lower social class origins.…”
Section: Hypothesesmentioning
confidence: 99%
“…It is an important issue in management education that necessitates intentional classroom design and additional research to minimize the education disparity for people with lower-social class origins. The recent JME special issue on Privilege includes an article addressing social class privilege (Moergen & Kish-Gephart, 2023), which is a great resource and stepping stone for management instructors and scholars. Finally, as previously mentioned, issues in social justice are less commonly explored in JME and business schools in general (Edmondson et al, 2020), so more work explicitly incorporating social justice would expand our perspectives and understanding.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…While some have a working-class background (we know this from their learning diaries), many are from middle-class or upper middle-class families, and most are white. Our idea of creating a "level playing field" is thus a relative notion (cf., Moergen & Kish-Gephart, 2023).…”
Section: Putting Privilege To Constructive Use?mentioning
confidence: 99%
“…While some have a working‐class background (we know this from their learning diaries), many are from middle‐class or upper middle‐class families, and most are white. Our idea of creating a “level playing field” is thus a relative notion (cf., Moergen & Kish‐Gephart, 2023). Many never get to participate in the first place due to broader systems of inequality related to educational access in Finland and elsewhere.…”
Section: Putting Privilege To Constructive Use?mentioning
confidence: 99%